A Question of Leadership Is There Such a Thing as an Asian, as Opposed to a Western, Style of Leadership - Jenkins, Michael; Jenkins, Michael; Chan, Carolyn (Center for Creative Leadership, 2004)
Given Asia's new interest in leadership, there is a growing demand for high-impact and ongoing leadership development programs in the region. However, leadership education providers need to be extremely careful not to impose a Western view of leadership on Asia.